Three new species of Amblyrhethus (Orthoptera, Grylloidea, Gryllidae, Paroecanthini) from Brazil - Campos, Lucas Denadai de; Mello, Francisco de Assis Ganeo de [UNESP] (Pensoft Publishers, 2022)
Amblyrhethus Kirby, 1906 is a genus of arboreal, undergrowth, and shrub crickets comprising, at present, seven species: one from Panama, one from Peru, two from Colombia, two from Brazil, and one with an un-precise locality. These crickets are seldom found in regular active collecting at night, although males produce a rather loud calling song. Unfortunately, their songs have never been recorded, and there is no ecological information for this genus so far. Here, we describe three new species from the Brazilian Atlantic Forest.
Keywords: Cricket; Neotropical; New taxa; South America; Taxonomy